2013
DOI: 10.3399/bjgp14x676429
|View full text |Cite
|
Sign up to set email alerts
|

Management of suspected infectious diarrhoea by English GPs: are they right?

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The GPs’ self-estimated proportion of requesting faecal specimens for 18% of patients is comparable to other studies where rates vary between 4.3% and 50% [ 25 , 28 , 31 33 ]. Individual rates differed strongly among the GPs interviewed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The GPs’ self-estimated proportion of requesting faecal specimens for 18% of patients is comparable to other studies where rates vary between 4.3% and 50% [ 25 , 28 , 31 33 ]. Individual rates differed strongly among the GPs interviewed.…”
Section: Discussionsupporting
confidence: 81%
“…Individual rates differed strongly among the GPs interviewed. The observed heterogeneity seems to be rather common and has also been observed among English GPs [ 31 ]. It is likely related to GPs’ individually perceived usefulness of stool diagnostic results for case management and the patient populations they serve.…”
Section: Discussionmentioning
confidence: 77%
“…The King’s Fund recently reported that practices performing well on delivering a good experience for their patients also perform well on measures of clinical quality. 20 In a recent English survey, 89% of GP responders ( n = 477) 21 reported giving verbal advice to patients on how to collect a stool specimen although only 2% gave written instructions; 22 this is despite the fact that it has been shown that screening compliance is significantly improved when patients have an information leaflet. 23 …”
Section: Discussionmentioning
confidence: 99%
“…However, comparing international rates is hampered by disparities in case definitions, study designs, periods of recall of symptoms and the characteristics of the populations studied [ 10 , 11 ]. Most people with IID do not seek medical attention [ 2 , 4 ], and even when they do their illness is often not investigated or reported [ 12 ], so it is difficult to determine accurately the population incidence of disease based on national surveillance or other routinely collected data.…”
Section: Introductionmentioning
confidence: 99%